„Ненормативные” средства выражения адресованности в школьной практике, или игра с нормой - Kravchenko, Bohdana (Studia Rossica Posnaniensia, 2024)
The article consists of several parts: an introduction, theoretical and practical parts, and the conclusion. This work touches upon several directions in linguistics. First of all, attention is paid to the concept of addressing, namely the terms addressee (Listener) and addresser (Speaker) and their interrelation at the moment of communication. The author provides a definition of human speech behavior, which at the present stage is usually considered in pragmalinguistics. The article focuses on the factor of the addresser in pedagogical discourse (the speech of a Russian language teacher at a secondary school in Slovakia is analyzed) from the point of view of observing the normativity of speech. In this regard, special attention is paid to the culture of speech and the concept of literary language. The work shows the varieties of norms of literary language, but the emphasis is on stylistic norms. The author focuses on the search for violations of stylistic norms in а scientific style. The article provides the author’s classification of selected language violations and characterizes the speech behavior of the Speaker.